Bioinspired nanocomposite films with graphene and MXene. (December 2022) - Li, Lei; Cheng, Qunfeng
Abstract: Two dimensional nanomaterials, such as graphene and MXene, have been widely used to fabricate high performance nanocomposite films owing to their unique structure and excellent physiochemical properties, showing enormous potential applications in many areas. However, the existing voids and wrinkling in the nanocomposite films inevitably impedes realizing the high performance of the nanocomposite films during the assembly process of graphene and MXene nanosheets. Nacre provides an inspiration for fabricating high performance graphene and MXene nanocomposite films through constructing a high alignment structure and strong interface interactions. In this review, we summarize the preparation approaches of graphene and MXene nanocomposite films and discuss the mechanical properties. Then, several effective strategies for assembling graphene and MXene nanosheets have been concluded and discussed. Meanwhile, we also summarize and discuss the applications of graphene and MXene nanocomposite films including electromagnetic interference (EMI) shielding and thermal management. Finally, outlooks and challenges are proposed to promote their progress and applications in the future. Graphical abstract: Image, graphical abstract